Off-label Drug Use in Neonatal Intensive Care Unit of a Tertiary Care Teaching Hospital in India - Sara Nasrollahi; Neelathahalli Kasturirangan Meera (International Journal of Pharma and Bio Sciences, 2020)
Neonates hospitalized in neonatal intensive care units (NICU) are exposed to various drugs most being off-labelled due to lack of pediatric specific formulations and labelling recommendations for newborns which can bring health risks. Neonates are generally excluded from clinical trials and prescription of most of drugs for neonates will be decided based on extrapolating the safety and efficacy data of use of drugs on adults which leads to off-label use of drugs among neonates. Offlabel refers to use of drug outside its authorised product license with respect to age, dose, indication, dosage and route of administration. Hence, this study was designed to assess the extent of off-label use of drugs among hospitalized neonates. This prospective observational study was conducted in the neonatal intensive care unit of a tertiary care teaching hospital in Bengaluru, India from January 2017 to January 2020.Details of administered drugs were collected from case sheets of neonates who were in NICU for more than 24 hours and were administered with at least one drug. Off-label categories (age, weight, dose, dosage form, frequency, indication, route of administration) were assessed by referring to Lexicomp database or packaging inserts. Total of 945 neonates were included in the study. It was found that 61.9% of all prescribed drugs were off-label. We found that 913 (96.6%) neonates received at least one off-label drug. Extremely preterm neonates had the highest exposure to at least one off-label drug. Dose (2010, 46%), followed by frequency (1338, 30.5%) and dosage form (495, 11.3%) were most commonly identified off-label categories. Off-label use of drugs was found to be a common practice in neonatal intensive care unit as in other countries. The active participation of clinical pharmacist with co-operation of pharmaceutical companies and healthcare members can work towards improvement in safe and rational use of drugs and minimising off-label prescription.